What’s Dog Got to Do With It? Motivation Behind Denominal (Animal) Verbs - Alisa Egorova; Hans-Georg Wolf (Research in Language)
This paper investigates the motivation behind denominal conversion of animal nouns to verbs as well as their resultant senses. Upon critical consideration of previous accounts of animal verb senses and their possible sources, the argument is put forward that animal verbs are not uniform in their semantics and cannot therefore be considered a separate conceptual category or analysed as such. Previous findings are then reinterpreted from the point of view of frame-based accounts of denominal conversion. Animal verbs are shown to be generated by the same grammatical generalisations as other denominal verbs of English, with their metaphoricity appearing to be a concomitant rather than a driving factor in the grammatical act of their conversion.